University and Exile in the 1970s: the Political Participation of Rodolfo Agoglia and Arturo Roig (2019)
In 1973, the Argentinian philosophers Rodolfo Agoglia and Arturo Roig participate in the institutionalization of pedagogical experiences that are critical of traditional teaching methods used in universities. Nevertheless they are fired from their jobs and exiled in the first months of 1976. The History of Latin American Ideas and Practical Philosophy offer methodological insights for this study, allowing the study of relations between university and exile in the context of the pedagogical transformations of the 1970s.